Highly permeable grouting liquid, preparation method and application thereof

CN122790201APending Publication Date: 2026-09-22XIONGYIDA (BEIJING) NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611230813.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0002]在隧道围岩、破碎岩体、煤矿软岩、地基微细裂隙等工程注浆施工中,传统亲水聚氨酯注浆液存在以下技术瓶颈:(1)纯聚氨酯浆液固结体脆性大、易开裂、抗渗性能差,长期使用易出现二次渗漏;(2)将常规纳米二氧化硅、碳材料与浆液直接物理共混,易出现严重团聚现象,不仅无法提升浆液性能,还会增大浆液粘度,丧失高渗透性能,无法渗透0.05mm以下超细裂隙;(3)现有纳米改性聚氨酯注浆液,纳米填料掺量高、制备工艺复杂、生产成本高,且凝胶时间难以精准调控,动水地层适配性差;(4)普通纳米改性注浆液分散稳定性差,易分层沉淀,现场施工适配性差

Benefits of technology

本发明提供了一种高渗透注浆液,包括A组分和B组分;所述A组分包括以下质量份数的原料:聚醚多元醇N220:45~55份,聚醚多元醇DL-2000:32~42份,氨基改性氧化石墨烯:0.005~0.03份,二乙醇胺:2~5份,消泡剂:0.2~0.5份,分散稳定剂:0.4~0.6份;所述B组分包括以下质量份数的原料:脲酮亚胺改性MDI:48~55份,聚醚多元醇N330:47~53份,有机锡催化剂:0.01~0.05份;所述A组分和B组分的质量比为0.9~1.1:0.9~1.1。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122790201A_ABST
    Figure CN122790201A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of geotechnical grouting materials, and particularly relates to a high-permeability grouting liquid and a preparation method and application thereof. The high-permeability grouting liquid comprises components A and B. The component A comprises the following raw materials in mass fractions: polyether polyol N220: 45-55 parts, polyether polyol DL-2000: 32-42 parts, amino-modified graphene oxide: 0.005-0.03 parts, diethanolamine: 2-5 parts, defoaming agent: 0.2-0.5 parts, and dispersion stabilizer: 0.4-0.6 parts. The component B comprises the following raw materials in mass fractions: uretonimine-modified MDI: 48-55 parts, polyether polyol N330: 47-53 parts, and organic tin catalyst: 0.01-0.05 parts. The mass ratio of the component A to the component B is 0.9-1.1:0.9-1.1. The grouting liquid has the synergistic effects of ultralow viscosity, ultrahigh permeability, high strength and toughness, and high impermeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of geotechnical grouting materials technology, specifically relating to a high-permeability grouting fluid, its preparation method, and its application. Background Technology

[0002] In the grouting construction of tunnel surrounding rock, fractured rock mass, soft rock in coal mines, and micro-fractures in foundations, traditional hydrophilic polyurethane grouting has the following technical bottlenecks: (1) Pure polyurethane grout solids are brittle, prone to cracking, and have poor impermeability, and are prone to secondary leakage after long-term use; (2) Direct physical mixing of conventional nano-silica and carbon materials with grout can easily lead to severe agglomeration, which not only fails to improve the performance of the grout but also increases the viscosity of the grout, loses high permeability, and cannot penetrate ultra-fine cracks below 0.05mm; (3) Existing nano-modified polyurethane grouting has high nanofiller content, complex preparation process, high production cost, and difficult gelation time control, resulting in poor adaptability to dynamic water formations; (4) Ordinary nano-modified grouting has poor dispersion stability, is prone to stratification and sedimentation, and has poor adaptability to on-site construction.

[0003] Currently, graphene-modified polyurethane grouting materials all adopt direct physical blending methods, which cannot fundamentally solve the technical problems of graphene sheet agglomeration, poor compatibility with polyurethane matrix, and thickening and seepage prevention. They also cannot achieve the synergistic effects of ultra-low viscosity, long-term sealing of ultra-micro cracks, and toughening and crack resistance. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a high-permeability grouting fluid, its preparation method, and its application. The polyurethane grouting fluid of this invention features ultra-low viscosity, ultra-high permeability, and high strength and toughening, making it suitable for penetration into ultra-micro fractures.

[0005] This invention provides a high-permeability grouting fluid, comprising component A and component B; Component A comprises the following raw materials in parts by weight: polyether polyol N220: 45-55 parts, polyether polyol DL-2000: 32-42 parts, amino-modified graphene oxide: 0.005-0.03 parts, diethanolamine: 2-5 parts, defoamer: 0.2-0.5 parts, and dispersant stabilizer: 0.4-0.6 parts; Component B comprises the following raw materials in parts by weight: urea-ketone imine modified MDI: 48-55 parts, polyether polyol N330: 47-53 parts, and organotin catalyst: 0.01-0.05 parts. The mass ratio of component A to component B is 0.9~1.1:0.9~1.1.

[0006] Preferably, the amino-modified graphene oxide is used in the form of an amino-modified graphene oxide dispersion, wherein the mass content of amino-modified graphene oxide in the amino-modified graphene oxide dispersion is 1.5%; the preparation method of the amino-modified graphene oxide dispersion includes the following steps: mixing graphene oxide powder, ethanol and aminosilane coupling agent to perform amino grafting, thereby obtaining the amino-modified graphene oxide dispersion.

[0007] Preferably, the mass ratio of the graphene oxide powder, ethanol and aminosilane coupling agent is 1.5:100:1.5.

[0008] Preferably, the preparation method of the urea-ketone imine modified MDI includes the following steps: under the action of triethyl phosphite catalyst, MDI is subjected to high-temperature decarbonization and medium-temperature ring-closing cyclization in sequence to obtain urea-ketone imine modified MDI; the high-temperature decarbonization temperature is 190±3℃, and the medium-temperature ring-closing cyclization temperature is 165~175℃.

[0009] Preferably, component B is an isocyanate prepolymer, wherein the mass content of isocyanate groups in the isocyanate prepolymer is 19-21%.

[0010] Preferably, component A and component B are packaged separately, and the mass ratio of component A to component B is 1:1.

[0011] Preferably, the polyurethane grout has an initial viscosity of 20~25 mPa·s, a gel time of 10s~30min, a permeable crack width ≤0.05mm, a solidified body compressive strength ≥15MPa, a solidified body impermeability grade ≥P12, and a water swelling rate of 15~25%.

[0012] The present invention also provides a method for preparing the high-permeability grouting fluid described in the above technical solution, comprising the following steps: Component A is obtained by mixing polyether polyol N220, polyether polyol DL-2000, amino-modified graphene oxide, diethanolamine, defoamer and dispersant stabilizer. Component B was obtained by mixing urea-ketone imine-modified MDI, polyether polyol N330, and organotin catalyst in a prepolymerization reaction.

[0013] Preferably, the temperature of the prepolymerization reaction is 65~75℃ and the time is 1.5~2.5h.

[0014] The present invention also provides a method for using the high-permeability grouting liquid described in the above technical solution, including method one or method two, wherein method one includes: After mixing components A and B, a single-liquid grout is injected, which gels upon reaching the construction site. The second method includes: Components A and B are injected in a two-component grouting process, which gels upon reaching the construction site.

[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a high-permeability grouting fluid, comprising component A and component B. Component A comprises the following raw materials in parts by weight: polyether polyol N220: 45-55 parts, polyether polyol DL-2000: 32-42 parts, amino-modified graphene oxide: 0.005-0.03 parts, diethanolamine: 2-5 parts, defoamer: 0.2-0.5 parts, and dispersion stabilizer: 0.4-0.6 parts. Component B comprises the following raw materials in parts by weight: urea-ketone imine-modified MDI: 48-55 parts, polyether polyol N330: 47-53 parts, and organotin catalyst: 0.01-0.05 parts. The mass ratio of component A to component B is 0.9-1.1:0.9-1.1.

[0016] This invention provides an amino-modified graphene oxide synergistically toughened ultra-low viscosity hydrophilic polyurethane high-permeability grouting fluid, which solves the technical defects of traditional nano-modified grouting fluids, such as graphene agglomeration, high viscosity, poor injectability, and insufficient impermeability and cracking of the solidified body. It achieves synergistic effects of dispersion without agglomeration, ultra-low viscosity, high permeability in ultra-micro fractures, adjustable gel time, toughening and crack resistance, and environmental friendliness and low toxicity. This grouting fluid is suitable for grouting, water plugging, and reinforcement projects in tunnels, mines, foundations with ultra-fine fractures, and water-rich strata.

[0017] The polyurethane grout of the present invention has at least the following advantages: (1) In-situ grafting of aminosilane coupling agent to modify graphene oxide: Through chemical bonding, graphene monolayers are uniformly dispersed, significantly inhibiting agglomeration. The amount of nanofiller is reduced to 0.005~0.03 parts by mass (accounting for 0.05 to 0.3 parts by mass of component A), greatly reducing costs without increasing slurry viscosity and ensuring ultra-high fluidity. (2) Ultra-low viscosity and ultra-micro penetration: The initial viscosity of the slurry is ≤25mPa·s, which can penetrate ≤0.05mm ultra-fine rock fissures, solving the industry problem that micro-fissures cannot be filled and are not sealed tightly; (3) Three-dimensional cross-linking toughening and crack resistance: Amino-modified graphene and polyurethane matrix form a three-dimensional cross-linking network, which greatly improves the toughness of the solidified body, without brittle cracking, impermeability grade ≥ P12, compressive strength ≥ 15MPa, and water plugging reinforcement is long-term and stable. (4) Precisely adjustable gel time: The gel time is continuously adjustable from 10s to 30min, which is suitable for various construction conditions such as low-pressure grouting, dynamic water formations, rapid sealing, and slow penetration; the grout has no bleeding, does not shrink, and expands when it comes into contact with water for sealing. (5) Environmentally friendly and low toxicity: The system does not contain volatile organic solvents, has no odor, and is suitable for environmentally friendly grouting scenarios such as groundwater, underground engineering, and mining tunnels. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 These are photographs of component A and component B in Example 1; Figure 2 This is a photograph of the mixture of component A and component B in Example 1. Figure 3 This is a photograph of the cured product after mixing and curing component A and component B in Example 1; Figure 4 Diagram of a dual-motor, dual-cylinder grouting machine; Figure 5 This is a cross-sectional flowchart of the industry-standard grouting simulation test method. Detailed Implementation

[0020] This invention provides a high-permeability grouting fluid, comprising component A and component B; Component A comprises the following raw materials in parts by weight: polyether polyol N220: 45-55 parts, polyether polyol DL-2000: 32-42 parts, amino-modified graphene oxide: 0.005-0.03 parts, diethanolamine: 2-5 parts, defoamer: 0.2-0.5 parts, and dispersant stabilizer: 0.4-0.6 parts; Component B comprises the following raw materials in parts by weight: urea-ketone imine modified MDI: 48-55 parts, polyether polyol N330: 47-53 parts, and organotin catalyst: 0.01-0.05 parts. The mass ratio of component A to component B is 0.9~1.1:0.9~1.1.

[0021] In this invention, component A and component B are preferably packaged separately, and the mass ratio of component A to component B is preferably 1:1.

[0022] The A component of this invention comprises the following raw materials in parts by weight: polyether polyol N220: 45-55 parts, polyether polyol DL-2000: 32-42 parts, amino-modified graphene oxide: 0.005-0.03 parts, diethanolamine: 2-5 parts, defoamer: 0.2-0.5 parts, and dispersant stabilizer: 0.4-0.6 parts.

[0023] In this invention, the preferred mass fraction of polyether polyol N220 in component A is 45-52 parts, specifically 45, 48, or 52 parts. The polyether polyol N220 can construct the basic framework: as a component of the soft segment of polyurethane, it provides the hydroxyl groups required for the reaction, reacting with isocyanate (modified MDI in component B) to form a polyurethane polymer; it regulates hardness and strength: compared to DL-2000, the structure of polyether polyol N220 can provide the material with higher mechanical strength and hardness, preventing the finished product from being too soft; it improves compatibility: it has good compatibility with other additives in the formulation (such as amino-modified graphene oxide and catalysts), stabilizing the system.

[0024] Based on the mass fraction of the polyether polyol N220, the preferred mass fraction of the polyether polyol DL-2000 is 32-40 parts, specifically 32, 36, or 40 parts. The polyether polyol DL-2000 is a difunctional hydrophilic polyether polyol, which can improve flexibility and elasticity: the long-chain polyether structure contains a large number of flexible ether bonds, providing excellent flexibility, resilience, and bending resistance to polyurethane materials; enhance hydrophilicity: the hydrophilic structure can improve the hydrophilicity of the material, enhance its dispersibility in water-based systems, and optimize its hydrolysis resistance; adjust processing performance: the low viscosity of DL-2000 can reduce the overall viscosity of component A, making the system easier to handle during mixing and application.

[0025] Based on the mass fraction of the polyether polyol N220, the mass fraction of the amino-modified graphene oxide is preferably 0.02 to 0.03 parts, specifically 0.0225 parts.

[0026] In this invention, the amino-modified graphene oxide is preferably used in the form of an amino-modified graphene oxide dispersion, and the mass solid content of the amino-modified graphene oxide in the dispersion is preferably 1.5%. The preparation method of the amino-modified graphene oxide dispersion includes the following steps: mixing graphene oxide powder, ethanol and an aminosilane coupling agent to perform amino grafting, thereby obtaining the amino-modified graphene oxide dispersion. The preferred mass ratio of the graphene oxide powder, ethanol, and aminosilane coupling agent is 1.5:100:1.5; the preferred aminosilane coupling agent is KH550 (γ-aminopropyltriethoxysilane), γ-aminopropylmethyldiethoxysilane, or N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane; the preferred reaction temperature for amino grafting is 60-70°C, and the preferred time is 2-3 hours. The amino grafting is preferably carried out under nitrogen protection, ultrasound, and stirring conditions, and the preferred power of the ultrasound is 800-1000W; the reaction after amino grafting preferably includes naturally cooling the resulting reaction solution to room temperature.

[0027] The reaction mechanism for preparing the amino-modified graphene oxide of this invention is as follows: the silane coupling agent first hydrolyzes to generate silanol groups, which then dehydrate and condense with hydroxyl groups on the graphene oxide surface to form Si-OC covalent bonds; simultaneously, the amino group undergoes ring-opening addition with the epoxy group to form CN bonds, achieving firm grafting of amino groups onto the graphene surface and improving dispersibility and reactivity. The modification process consists of three steps: (1) Hydrolysis reaction: Silane ethoxy groups hydrolyze in a trace amount of water environment to generate silanol groups; ; (2) Condensation reaction: silanol groups dehydrate and condense with hydroxyl groups on the surface of graphene oxide to form stable silicon-oxygen-carbon covalent bonds, thus achieving molecular grafting; ; (3) Ring-opening addition reaction: The amino group carried by silane attacks the epoxy group on the surface of graphene oxide, the epoxy ring opens and forms carbon-nitrogen bond, and finally the amino active group is firmly introduced on the surface of graphene sheet.

[0028] This invention uses amino-modified graphene oxide, which significantly reduces the tendency to agglomerate and can be uniformly dispersed in polyether systems. At the same time, it reserves active reaction sites, which can chemically bond with the polyurethane matrix and improve the interfacial bonding strength.

[0029] Based on the mass fraction of the polyether polyol N220, the mass fraction of the diethanolamine is preferably 2 to 4.5 parts, specifically 2 parts, 3.5 parts, or 4.5 parts.

[0030] Based on the mass fraction of the polyether polyol N220, the mass fraction of the defoamer is preferably 0.2 to 0.4 parts, specifically 0.3 parts. The defoamer is preferably a non-silicone defoamer or an organosilicone polyether defoamer (polysiloxane-polyether copolymer type, such as BYK-024); the defoamer can defoam and suppress air bubbles generated during stirring or grouting.

[0031] Based on the mass fraction of the polyether polyol N220, the mass fraction of the dispersing stabilizer is preferably 0.5 parts. The dispersing stabilizer is preferably a mixture of a polyether-type dispersing stabilizer (BYK-163) and a nonionic surfactant stabilizer (fatty alcohol oxyethylene ether) in a mass ratio of 1:1; the dispersing stabilizer can prevent the precipitation of amino-modified graphene oxide powder.

[0032] The B component of this invention comprises the following raw materials in parts by weight: 48-55 parts of urea-ketone imine modified MDI, 47-53 parts of polyether polyol N330, and 0.01-0.05 parts of organotin catalyst.

[0033] In this invention, component B is an isocyanate prepolymer, and the mass content of NCO (isocyanate group) in the isocyanate prepolymer is preferably 19-21%, specifically 19%, 20% or 21%.

[0034] In this invention, the mass fraction of urea-ketone imine-modified MDI in the raw material of component B is preferably 48 to 53 parts, specifically 48 parts, 50.5 parts, or 53 parts.

[0035] In this invention, the preparation method of the urea-ketone imine modified MDI includes the following steps: under the action of triethyl phosphite catalyst, MDI is subjected to high-temperature decarbonization and medium-temperature ring-closing cyclization sequentially to obtain urea-ketone imine modified MDI; the high-temperature decarbonization temperature is 190±3℃ and the time is 1.8h; the medium-temperature ring-closing cyclization temperature is 165~175℃ and the time is 2h.

[0036] In this invention, the urea-ketone imine-modified MDI comprises the following raw materials in parts by weight: 99.82~99.94 parts of 4,4'-pure MDI (melt grade, melting point 40°C), 0.04~0.12 parts of triethyl phosphite (a catalyst for cyclization catalysis), and 0.02~0.06 parts of 85wt% phosphoric acid (a reaction terminator).

[0037] This invention uses 4,4'-pure MDI (4,4'-diphenylmethane diisocyanate) as a matrix and prepares highly stable urea-ketone imine-modified liquid MDI through a two-step controlled self-polymerization reaction involving high-temperature catalytic decarbonization and temperature-controlled ring-closing cyclization. The reaction mechanism consists of two steps: (1) Two MDI molecules with terminal NCO groups undergo carbon dioxide removal under high temperature and phosphorus-based catalyst to generate carbodiimide (CDI) active intermediate: 2MDI-NCO → CDI + CO2; (2) The generated carbodiimide further undergoes a nucleophilic cyclization reaction with free MDI-NCO to construct a ternary cyclic latent active structure of urea ketimide (UTI): CDI + MDI-NCO → Urea ketone imine three-membered ring; This invention regulates the reaction depth by precisely controlling the temperature and periodically monitoring the NCO content, thereby stabilizing the proportion of urea-ketone imine structure in the system at 5-12%, ultimately producing a modified MDI product. The product's core indicators are: NCO mass fraction 27.0-27.8% and average functionality 2.18-2.25.

[0038] The modified MDI of this invention is a carbodiimide-urea ketimide cyclic modified liquid MDI obtained by controlled partial self-polymerization modification with a phosphorus-based catalyst using 4,4'-molten pure MDI as raw material. During the reaction, the MDI molecule first undergoes decarburization to generate a carbodiimide intermediate, and then forms a stable ternary urea ketimide ring structure by cyclization with the residual NCO group. The product is liquid at room temperature and has no tendency to crystallize, and its performance differs from ordinary low-content urea ketimide liquefied MDI and multifunctional PAPI polymerized MDI.

[0039] The modified MDI of this invention has a latent three-membered ring active group built into the molecular chain, which has extremely strong stability at room temperature and no side reactions. When the system comes into contact with active groups such as hydroxyl and amino groups, the ring structure opens and releases highly active NCO to participate in the cross-linking reaction, thus taking into account both storage stability and later reaction activity.

[0040] In this embodiment of the invention, the preparation method of the urea-ketone imine-modified MDI includes the following steps: (1) Melting and dehydration process The reactor was sealed and nitrogen gas was introduced to establish a slight positive pressure (nitrogen pressure 0.02~0.05 MPa). Solid pure MDI raw material was added; the temperature was raised to 50~55℃ to completely melt the material, and the mixture was stirred at a constant temperature for 30 min. Subsequently, a high vacuum (-0.095MPa) dehydration treatment was initiated, and the moisture content of the material in the reactor was strictly controlled to be <100 ppm to completely eliminate the interference of moisture on the NCO side reaction.

[0041] (2) High-temperature catalytic decarbonization (generating carbodiimide intermediate) The dehydrated material was heated to 190±3℃, and a metered amount of triethyl phosphite catalyst was added at once. The reaction was kept at a constant temperature for 1.8~2.5h. The NCO at the MDI end group underwent a decarbonylation reaction, and the system generated a highly active carbodiimide (CDI) intermediate, which provides a precursor for the subsequent ring-closure reaction.

[0042] (3) Medium-temperature closed-loop circulatory process (core controlled process) The temperature was lowered to 165~175℃ for isothermal closed-loop reaction, and the reaction time was 2.0~3.0h. Carbodiimide in the system fully cyclized with free MDI-NCO to generate a stable urea ketone imine three-membered ring structure.

[0043] The NCO content was sampled every 30 minutes to monitor the degree of modification reaction in real time and precisely control the mass fraction of urea ketone imine structure to 7~10%.

[0044] Currently, the urea-ketone imine content of conventional liquefied MDI on the market is generally less than 5%. This invention significantly increases the proportion of cyclic active structures and improves product performance through step-by-step temperature-controlled reaction in steps (2) and (3).

[0045] (4) Reaction termination, cooling, filtration and filling When the NCO content of the material is stable within the qualified range of 27.0~27.8%, a small amount of 85% phosphoric acid terminator is added to quench the catalytic activity and terminate the reaction; the temperature is rapidly reduced to below 60℃, and impurities are removed by filtration through a 120-mesh filter. Finally, the product is sealed with nitrogen to prevent moisture from entering the container, resulting in a highly stable modified MDI product (modified MDI discharge NCO 27.0~27.8%).

[0046] Based on the mass fraction of urea-ketone imide modified MDI, the preferred mass fraction of polyether polyol N330 is 47.5 to 52 parts, specifically 47.5, 50, or 52 parts. The polyether polyol N330 provides crosslinking sites: it has three hydroxyl functional groups, and when reacting with isocyanate (urea-ketone imide modified MDI), it can form a three-dimensional crosslinked network structure, increasing the crosslinking density of the polyurethane material and enhancing its strength, hardness, heat resistance, and dimensional stability. It also regulates system viscosity and compatibility: polyether polyol N330 and modified MDI have good compatibility, which can adjust the overall viscosity of component B, making the mixing of components A and B more uniform and improving construction and processing performance. Furthermore, it optimizes the material's mechanical properties: the crosslinked structure can improve the material's compressive strength and tear resistance, preventing excessive deformation under stress, and also improving the material's solvent resistance and aging resistance.

[0047] Based on the mass fraction of urea-nitrogenimide-modified MDI, the mass fraction of the organotin catalyst is preferably 0.03 to 0.05 parts, specifically 0.02 parts, 0.04 parts, or 0.05 parts. The organotin catalyst is preferably dibutyltin dilaurate (DBTDL). The gelation time (approximately tens of seconds to several minutes) can be adjusted by changing the amount of organotin catalyst in component B.

[0048] The polyurethane grout of this invention has an initial viscosity of 20-25 mPa·s and a gel time of 10-30 min (precisely controlled by adjusting the amount of catalyst in component B). A high catalytic content (0.04-0.05 parts) enables ultra-fast gelation (10-5 min, rapid sealing of flowing water). A representative example is Example 3: 0.05 parts organotin, with a gel time of only 30 seconds. The high tin content significantly accelerates the cross-linking reaction of NCO with hydroxyl and amino groups, resulting in instantaneous thickening and solidification after mixing, suitable for emergency sealing of leaks caused by gushing water or high-pressure flowing water. A medium catalytic content (0.03-0.04 parts) enables medium-speed gelation. The grout (5-20 min, conventional micro-fracture grouting), representative example 1: 0.04 parts organotin, gelling for 5 min; balancing penetration time and curing speed, it is a common formula for conventional grouting in tunnels and foundations; a low catalytic amount (0.01-0.03 parts) can achieve slow gelation (15-30 min, low-pressure long-distance penetration), representative example 2: 0.02 parts organotin, gelling for 18 min after adjusting the polyol ratio; the reduced tin content slows down the reaction rate, allowing sufficient time for the grout to penetrate deep into 0.04-0.05 mm ultra-fine fractures, suitable for deep rock strata and long-distance low-pressure grouting. The grouting fluid of this invention can penetrate fractures ≤0.05 mm wide, with a consolidated body compressive strength ≥15 MPa, a consolidated body impermeability grade ≥P12, a water swelling rate of 15-25%, and the consolidated body is free of cracks and brittle fractures, providing long-term seepage resistance.

[0049] This invention provides a method for preparing the polyurethane grout described in the above technical solution, comprising the following steps: Component A is obtained by mixing polyether polyol N220, polyether polyol DL-2000, amino-modified graphene oxide, diethanolamine, defoamer and dispersant stabilizer. Component B was obtained by mixing urea-ketone imine-modified MDI, polyether polyol N330, and organotin catalyst in a prepolymerization reaction.

[0050] Unless otherwise specified, all materials and equipment used in this invention are commercially available products in the field.

[0051] The present invention mixes polyether polyol N220, polyether polyol DL-2000, amino-modified graphene oxide, diethanolamine, defoamer and dispersant stabilizer to obtain component A.

[0052] In this invention, the polyether polyols N220 and DL-2000 are preferably vacuum dehydrated before use, and the moisture content of the raw materials after vacuum dehydration is ≤0.05%. When the amino-modified graphene oxide is used in the form of a dispersion, the solvent in the dispersion is preferably removed simultaneously with the dehydration of the polyether polyols N220 and DL-2000. The vacuum dehydration temperature is preferably 100~110℃, and the time is preferably 2 hours. The mixing temperature is preferably 40~50℃, and the time is preferably 30~40 minutes.

[0053] In this invention, urea-ketimide-modified MDI, polyether polyol N330, and organotin catalyst are mixed and subjected to a prepolymerization reaction to obtain component B.

[0054] In this invention, the polyether polyol N330 is preferably vacuum dehydrated before use, and the moisture content of the raw material after vacuum dehydration is ≤0.05%; the vacuum dehydration temperature is preferably 100~110℃, and the vacuum degree is preferably -0.095~-0.1MPa.

[0055] In this invention, urea-ketimine-modified MDI and organotin catalyst are preferably added dropwise to a reactor containing polyether polyol N330, and the dropwise addition time is preferably 30-40 min.

[0056] In this invention, the prepolymerization reaction temperature is preferably 65~75℃, and the time is preferably 1.5~2.5h, specifically 2h. The prepolymerization reaction is preferably carried out under nitrogen protection. The NCO mass content in the material after the prepolymerization reaction is preferably 19~21%, specifically 20%. The process after the prepolymerization reaction preferably includes: vacuum degassing at a system temperature below 50℃; the vacuum degassing pressure is -0.1MPa, and the time is 30min.

[0057] The present invention also provides the application of the high-permeability grouting fluid described in the above technical solution or the high-permeability grouting fluid obtained by the above preparation method in rock and soil grouting.

[0058] The present invention also provides a method for using the high-permeability grouting liquid described in the above technical solution, including method one or method two, wherein method one includes: After mixing components A and B, a single-liquid grout is injected, which gels upon reaching the construction site. The second method includes: Components A and B are injected in a two-component grouting process, which gels upon reaching the construction site.

[0059] In this invention, the mass ratio of component A to component B is preferably 1:1.

[0060] This invention provides an amino-modified graphene oxide synergistically toughened ultra-low viscosity hydrophilic polyurethane high-penetration grouting fluid. The mechanism of action of the polyurethane grouting fluid is as follows: (1) Mechanism of action of component A: The polyether polyol is first dehydrated under high temperature and vacuum to remove free water from the system, avoiding foaming and bursting problems caused by side reactions of water and isocyanate. The amino-modified graphene oxide is exfoliated by ultrasound and stably dispersed in the polyether matrix by hydrogen bonding and intermolecular forces, without increasing the overall viscosity of the slurry. Diethanolamine, as a hydrophilic chain extender, can participate in subsequent cross-linking reactions with active hydrogen in the molecule, and at the same time endow the slurry with hydrophilic response characteristics; the organotin catalyst can regulate the addition reaction rate and realize flexible adjustment of gelation time; the synergistic effect of various additives ensures the stability of slurry storage and no stratification precipitation.

[0061] (2) Synthesis mechanism of component B prepolymer: Under a nitrogen inert atmosphere, modified MDI isocyanate undergoes addition polymerization with trifunctional polyether polyol, and the isocyanate group combines with the hydroxyl group to form a urethane structure: ; By controlling the temperature and duration of the reaction process, a prepolymer with isocyanate end groups was prepared, allowing for precise control of the NCO content range. The trifunctional raw materials can construct a slightly branched cross-linked structure, effectively improving the mechanical strength and water resistance of the solidified body.

[0062] (3) Mechanism of two-component mixed curing and toughening sealing: After mixing components A and B, hydroxyl groups and isocyanates form urethane bonds; amino groups on the graphene surface react with isocyanates to form urea bonds. The amino-modified graphene uses a sheet structure as a cross-linking node, which acts like a nano-bridged skeleton to connect polyurethane molecular chains, forming a dense three-dimensional composite network that hinders crack propagation and achieves toughening and crack resistance. In aquifers, unreacted NCO reacts with water to generate amino groups and release carbon dioxide, which promotes moderate expansion of the solidified body (expansion rate 15~25%), tightly filling the fine cracks and voids, and improving the sealing density and impermeability.

[0063] To further illustrate the present invention, the high-permeability grouting fluid, its preparation method, and its application provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0064] Example 1 1. Preparation of amino-modified graphene oxide dispersion (one-step method) The mass ratio of graphene oxide (GO) powder, anhydrous ethanol, and KH550 is 1.5:100:1.5. (1) Add GO powder, anhydrous ethanol and KH550 to a nitrogen-protected reaction vessel in proportion and stir to premix evenly; (2) Heat to 60°C, and simultaneously turn on high-power ultrasound (800W) and stir, react for 2 hours; (3) Cool naturally to room temperature to obtain amino-modified graphene oxide dispersion (amino-modified GO mass solid content is 1.5%). Store in a sealed and light-proof environment under nitrogen protection (Note: amino-modified graphene oxide dispersion should be prepared and used immediately. If storage is required, it should be stored at 4~8℃, sealed and light-proof, under nitrogen protection, and the storage period should not exceed 30 days).

[0065] 2. Component A (Base Liquid) By weight, it includes: polyether polyol N220: 45 parts, polyether polyol DL-2000: 40 parts, amino-modified graphene oxide dispersion: 1.5 parts, diethanolamine: 2 parts, defoamer (BYK-024): 0.3 parts, and dispersion stabilizer (BYK-163 and fatty alcohol oxyethylene ether in a 1:1 mass ratio): 0.5 parts; The preparation method of component A includes the following steps: (1) Add polyether polyol N220, DL-2000 and the pre-prepared amino-modified graphene oxide dispersion into the reaction vessel; (2) Heat to 100℃ and vacuum dehydrate for 2 hours (to remove water and ethanol from the dispersion) until the water content is ≤0.05%; (3) Cool down to 40°C, add diethanolamine, dispersant stabilizer and defoamer, stir at constant temperature for 30 minutes; cool to room temperature, discharge and seal.

[0066] 3. Component B (modified isocyanate curing agent, NCO content in the prepolymer is 20%) By weight, it includes: 50.5 parts of urea-ketone imine-modified MDI, 50 parts of polyether polyol N330, and 0.04 parts of organotin catalyst; The preparation method of the urea-ketimine modified MDI (the raw materials, by weight, include MDI: 99.94 parts, triethyl phosphite: 0.04 parts, and 85wt% phosphoric acid: 0.02 parts) includes the following steps: (1) Melting and dehydration process The reactor was sealed and nitrogen gas was introduced to establish a slight positive pressure (nitrogen pressure 0.05 MPa). Solid pure MDI raw material was added, and the temperature was raised to 50°C to completely melt the material. The mixture was stirred at a constant temperature for 30 minutes. Subsequently, a high vacuum (-0.095 MPa) dehydration treatment was initiated, and the moisture content of the material in the reactor was strictly controlled to be <100 ppm to completely eliminate the interference of moisture on the NCO side reaction.

[0067] (2) High-temperature catalytic decarbonization (generating carbodiimide intermediate) The dehydrated material was heated to 190±3℃, and a metered amount of triethyl phosphite catalyst was added at once. The reaction was kept at a constant temperature for 1.8 h. The NCO terminal group of MDI underwent a decarbonylation reaction, and the system generated a highly active carbodiimide (CDI) intermediate, which provides a precursor for the subsequent ring-closure reaction.

[0068] (3) Mesothermal closed-loop cyclization The temperature was lowered to 165℃ for an isothermal closed-loop reaction, and the reaction time was 2.0 h. Carbodiimide in the system fully cyclized with free MDI-NCO to form a stable urea ketimide three-membered ring structure.

[0069] The NCO content was sampled every 30 minutes to monitor the degree of modification reaction in real time and precisely control the mass fraction of urea ketone imine structure to 7~10%.

[0070] (4) Reaction termination, cooling, filtration and filling When the NCO content of the material is stable within the acceptable range of 27.0~27.8%, 85% phosphoric acid terminator is added dropwise to quench the catalytic activity and terminate the reaction; the temperature is rapidly reduced to below 60℃, and impurities are removed by filtration through a 120-mesh filter. Finally, the modified MDI is obtained by nitrogen sealing to prevent moisture from entering the container.

[0071] The preparation method of component B includes the following steps: (1) Pretreatment of polyether polyol N330: vacuum dehydration at 100℃ and -0.095MPa until the moisture content is ≤0.05%, and then cooling to 50℃ under nitrogen protection for later use; (2) Add the dehydrated N330 to the reactor and stir at 40°C under nitrogen protection; (3) Slowly add modified MDI, control the addition time to 30 min, and keep the temperature ≤ 60℃, while adding organotin liquid catalyst; (4) After the addition is complete, raise the temperature to 70±5℃ and keep it warm for 2 hours. During this period, take a sample every 0.5 hours to measure the NCO value. (5) When the NCO content reaches 20%, cool down to below 50℃, vacuum degas (-0.1MPa, 30min), filter and seal the package under nitrogen protection.

[0072] The determination of NCO content refers to GB / T 12009.4-2016 "Determination of total chlorine content and isocyanate content in isocyanates of plastic polyurethane raw materials".

[0073] The mass ratio of component A to component B is 1:1.

[0074] Finished product performance: The test methods are shown in Table 1, and the test results are as follows: Viscosity: 22 mPa·s; Gel time: 5 min; Compressive strength: 16.8 MPa; Impermeability grade: P12 (corresponding to impermeability pressure ≥ 1.2 MPa); Can penetrate 0.04 mm micro-cracks.

[0075] Table 1 Relevant Test Methods

[0076] Example 2 The difference from Example 1 is that the ratio of component A and component B and the preparation method are the same as in Example 1.

[0077] By weight, component A includes: polyether polyol N220: 48 parts, polyether polyol DL-2000: 32 parts, amino-modified graphene oxide dispersion: 1.5 parts, diethanolamine: 3.5 parts, defoamer: 0.3 parts, and dispersion stabilizer: 0.5 parts; By weight, component B includes: 48 parts of urea-ketimine modified MDI, 52 parts of polyether polyol N330, and 0.02 parts of organotin catalyst; thus obtaining a prepolymer with an NCO content of 19%.

[0078] The mass ratio of component A to component B is 1:1.

[0079] Finished product performance: Viscosity: 21 mPa·s; gel time: 18 min; compressive strength: 15.2 MPa; it has a long-term permeability sealing effect, which means that the solidified body does not crack, is resistant to high-pressure water, can expand twice in dry and wet cycles, and has no decrease in anti-permeability over a long period of time; under normal and stable underground surrounding rock conditions in actual engineering, a single grouting can provide long-term sealing for 15 to 25 years. The test results are shown in Tables 2 and 3.

[0080] Table 2 Results of impermeability, wet-dry cycle resistance and long-term compression creep test

[0081] As can be seen from Table 2, the results of impermeability, wet-dry cycle resistance and long-term compression creep test meet the standards, thus it can be inferred that the high-permeability grouting liquid product of Example 2 can provide long-term sealing for 15 to 25 years after a single grouting.

[0082] Table 3. Accelerated aging test results

[0083] Based on the Arrhenius equation (the reaction rate increases by about 2 times for every 10°C increase in temperature), 70°C × 90d ≈ 25~30 years of equivalent aging at room temperature (20°C). Therefore, it is estimated that the product durability of the high-permeability grouting liquid of this invention can reach more than 25 years.

[0084] Compared to ordinary unmodified polyurethane (which leaks again after 3-8 years), the durability of the high-penetration grouting fluid of this invention is improved by 2-3 times.

[0085] Example 3 The difference from Example 1 is that the ratio of component A and component B and the preparation method are the same as in Example 1.

[0086] By weight, component A includes: polyether polyol N220: 52 parts, polyether polyol DL-2000: 36 parts, amino-modified graphene oxide dispersion: 1.5 parts, diethanolamine: 4.5 parts, defoamer: 0.3 parts, and dispersion stabilizer: 0.5 parts; By weight, component B includes: 53 parts of urea-ketone imine-modified MDI, 47.5 parts of polyether polyol N330, and 0.05 parts of organotin catalyst; thus obtaining a prepolymer with an NCO content of 21%.

[0087] The mass ratio of component A to component B is 1:1.

[0088] Finished product performance: Viscosity: 24 mPa·s; gel time: 30 s; compressive strength: 17.5 MPa; can be used for rapid sealing of moving water.

[0089] Comparative Example 1 (Blank group: pure hydrophilic polyurethane, without the addition of modified nanofillers) The only difference from Example 1 is that amino-modified graphene oxide is not added to component A, while the proportions of the other raw materials are the same as in Example 1. The preparation process does not involve amino modification.

[0090] Comparative Example 2 (Ordinary physical blending: unmodified graphene oxide directly doped) The only difference from Example 1 is that the amino-modified graphene oxide in component A is replaced with an equal amount of graphene oxide (0.0225 parts), while the other raw material ratios are the same as in Example 1. Preparation method of component A: Graphene oxide and polyether polyol are directly mixed by stirring; no amino modification process is required, and the rest of the preparation process is the same as in Example 1.

[0091] Comparative Example 3 (Conventional nano-SiO2 modification: ordinary nano-silicon modified polyurethane) The only difference from Example 1 is that the amino-modified graphene oxide in component A is replaced with an equal amount of ordinary nano-SiO2 (0.0225 parts), while the other raw material ratios are the same as in Example 1. The preparation process does not involve amino modification.

[0092] Application Example 1: Method of Using Slurry Mix components A and B thoroughly, then mix components A and B at a mass ratio of 1:1 and quickly inject the mixture into the construction area using a two-liquid grouting device.

[0093] Figure 1 These are photographs of component A and component B of the sample solution in Example 1. Figure 2 This is a photo of the mixture of component A and component B. Figure 3 This is a photo of the cured product.

[0094] Figure 4 This diagram shows a dual-motor, dual-cylinder grouting machine, including an A-component delivery pump, a B-component delivery pump (two independent metering pumps), a static mixer, high-pressure grouting pipeline, and a pressure gauge (0~0.5MPa low-pressure grouting). Pumps A and B deliver grout synchronously → the static mixer performs 1:1 homogenization → the mixed grout is delivered immediately. The gelation time after mixing is 10s~30min, with a short mixing section to avoid pipeline blockage.

[0095] Figure 5 This is a cross-sectional flowchart of the industry-standard grouting simulation test method.

[0096] Table 4 shows the test results of each embodiment and comparative example (where the solidified body was formed at room temperature of 25°C and cured for 7 days).

[0097] Table 4 Test results for each embodiment and comparative example

[0098] As can be seen from the data in Table 4: (1) Examples 1-3: The grout has extremely low viscosity and excellent dispersibility, and can penetrate 0.04-0.05mm ultrafine cracks. Its compressive strength and impermeability are far superior to conventional grouting materials. The solidified body has excellent toughness and no cracking. (2) Comparative Example 1 (pure polyurethane): poor overall performance, poor fissure permeability, low strength, easy to crack, completely unsuitable for micro-fissure grouting. (3) Comparative Example 2 (ordinary unmodified graphene): The graphene was severely agglomerated, which greatly increased the viscosity of the slurry, had extremely poor permeability, and had a very poor modification effect; (4) Comparative Example 3 (conventional nano SiO2): The slurry has high viscosity and poor injectability, and its performance improvement is limited, which cannot meet the requirements for sealing ultra-micro cracks.

[0099] This invention solves the problem of nanofiller agglomeration from the root by in-situ covalently modifying graphene with amino groups, achieving a synergistic effect of ultra-low viscosity, ultra-high permeability, high strength and toughness, and high impermeability.

[0100] Comparative Example 4 (using carbodiimide-modified MDI instead of urea-ketimide-modified MDI) The only difference from Example 1 is that the urea-ketimine modified MDI in component B is replaced with carbodiimine modified liquefied MDI, while the other raw material ratios and preparation processes are the same as in Example 1.

[0101] Finished product performance: The grout viscosity increased to 41 mPa·s, the grouting of the 0.04 mm micro-cracks was incomplete, the compressive strength of the consolidated body was 13.1 MPa, and the impermeability grade was P9.

[0102] Comparative Example 5 (MDI modified with PAPI partially replacing urea-ketimine) The only difference from Example 1 is that 30 wt% of the urea-ketimine modified MDI in component B is replaced with PAPI (polymethylene polyphenyl polyisocyanate), while the remaining raw material ratios and preparation processes are the same as in Example 1.

[0103] Finished product performance: The slurry viscosity surged to over 58 mPa·s, the amino-modified graphene oxide showed obvious agglomeration and sedimentation, the 0.04 mm micro-cracks were difficult to penetrate, the compressive strength was 13.8 MPa, and the impermeability grade was P10.

[0104] As can be seen from the data of Example 1 and Comparative Examples 4-5, Example 1 has extremely low viscosity, ultra-high penetration and significant toughening effect. The reasons may be: (1) Cyclic urea ketimide plays a molecular isolation role: it destroys the regular molecular arrangement of MDI, greatly reduces the viscosity of the prepolymer, and achieves ultra-low viscosity and ultra-fine crack penetration; ordinary commercially available conventional liquefied MDI is only slightly modified, and PAPI has high functionality and rigidity of polybenzene rings, so the slurry is thick and does not easily penetrate into microcracks. (2) Latent ring-opening activity: the urea ketimide ring gently opens and grafts with the amino group (-NH2) on the surface of GO, the interface is firmly bonded, and the aggregation and sedimentation of GO sheets are prevented; ordinary MDI / PAPI reacts too quickly, local cross-linking and agglomeration occur, and the graphene dispersion deteriorates.

[0105] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on the present invention without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A high-permeability grouting fluid, characterized in that, Includes component A and component B; Component A comprises the following raw materials in parts by weight: polyether polyol N220: 45-55 parts, polyether polyol DL-2000: 32-42 parts, amino-modified graphene oxide: 0.005-0.03 parts, diethanolamine: 2-5 parts, defoamer: 0.2-0.5 parts, and dispersant stabilizer: 0.4-0.6 parts; Component B comprises the following raw materials in parts by weight: urea-ketone imine modified MDI: 48-55 parts, polyether polyol N330: 47-53 parts, and organotin catalyst: 0.01-0.05 parts. The mass ratio of component A to component B is 0.9~1.1:0.9~1.

1.

2. The high-permeability grouting fluid according to claim 1, characterized in that, The amino-modified graphene oxide is used in the form of an amino-modified graphene oxide dispersion, wherein the mass content of amino-modified graphene oxide in the amino-modified graphene oxide dispersion is 1.5%; the preparation method of the amino-modified graphene oxide dispersion includes the following steps: mixing graphene oxide powder, ethanol and aminosilane coupling agent to perform amino grafting, thereby obtaining the amino-modified graphene oxide dispersion.

3. The high-permeability grouting fluid according to claim 2, characterized in that, The mass ratio of the graphene oxide powder, ethanol, and aminosilane coupling agent is 1.5:100:1.

5.

4. The high-permeability grouting fluid according to claim 1, characterized in that, The preparation method of the urea-ketone imine modified MDI includes the following steps: under the action of triethyl phosphite catalyst, MDI is subjected to high-temperature decarbonization and medium-temperature ring-closing cyclization in sequence to obtain urea-ketone imine modified MDI; the high-temperature decarbonization temperature is 190±3℃, and the medium-temperature ring-closing cyclization temperature is 165~175℃.

5. The high-permeability grouting fluid according to claim 1, characterized in that, Component B is an isocyanate prepolymer, and the mass content of isocyanate groups in the isocyanate prepolymer is 19-21%.

6. The polyurethane grout according to claim 1, characterized in that, Component A and Component B are packaged separately, and the mass ratio of Component A to Component B is 1:

1.

7. The high-permeability grouting fluid according to claim 1, characterized in that, The polyurethane grout has an initial viscosity of 20~25 mPa·s, a gel time of 10s~30min, a permeable crack width ≤0.05mm, a solidified body compressive strength ≥15MPa, a solidified body impermeability grade ≥P12, and a water swelling rate of 15~25%.

8. The method for preparing the high-permeability grouting fluid according to any one of claims 1 to 7, characterized in that, Includes the following steps: Component A is obtained by mixing polyether polyol N220, polyether polyol DL-2000, amino-modified graphene oxide, diethanolamine, defoamer and dispersant stabilizer. Component B was obtained by mixing urea-ketone imine-modified MDI, polyether polyol N330, and organotin catalyst in a prepolymerization reaction.

9. The preparation method according to claim 8, characterized in that, The prepolymerization reaction is carried out at a temperature of 65-75°C for 1.5-2.5 hours.

10. The method of using the high-permeability grouting fluid according to any one of claims 1 to 7, characterized in that, This includes either method one or method two, wherein method one includes: After mixing components A and B, a single-liquid grout is injected, which gels upon reaching the construction site. The second method includes: Components A and B are injected in a two-component grouting process, which gels upon reaching the construction site.